2016
DOI: 10.1007/s00520-016-3310-3
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of cardiovascular toxicity risks in cancer patients on selected targeted agents

Abstract: Several of the targeted agents were significantly associated with increased risk of specific cardiovascular toxicities, CHF, DLVEF, and HTN. Several had significant increased risk for high-grade cardiovascular toxicities (CHF, DLVEF, and HTN). Patients receiving such therapy should be closely monitored for these toxicities and early and aggressive treatment should occur. However, clinical experience has demonstrated that some of these toxicities may be reversible and due to secondary effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 147 publications
0
15
0
Order By: Relevance
“…More than half (40 out of 77) of the clinical trials included in the analysis utilized bevacizumab as the drug of treatment (65). Another meta-analysis showed that bevacizumab resulted in a significant decrease in EF with relative risk index of 3.4 (66). …”
Section: Hfmentioning
confidence: 99%
“…More than half (40 out of 77) of the clinical trials included in the analysis utilized bevacizumab as the drug of treatment (65). Another meta-analysis showed that bevacizumab resulted in a significant decrease in EF with relative risk index of 3.4 (66). …”
Section: Hfmentioning
confidence: 99%
“…Since sorafenib causes cardiotoxicity necessitating drug discontinuation in some patients (Schmidinger et al, ; Hall et al, ; Escalante et al, ), as well as liver toxicity associated with mitochondrial dysfunction in rodents (Zhang et al, ), we applied a non‐targeted metabolomics analysis using GC/MS to both the heart and liver after 2 weeks of treatment that induced cardiac toxicity (Figure ). We assayed skeletal muscle (quadriceps femoris) and plasma collected in parallel to identify if myocardium and striated muscle metabolism are affected similarly and if any of these observed alterations could be monitored by any biomarkers in the plasma.…”
Section: Resultsmentioning
confidence: 99%
“…Sorafenib is a KI that targets multiple kinases, including VEGFR, PDGFR, c‐Raf (Raf‐1)/B‐Raf, c‐Kit and FLT3 and is used to treat patients with advanced renal cell carcinoma, hepatocellular carcinoma and radioactive iodine resistant thyroid carcinoma (Wilhelm et al, ; Keating and Santoro, ; Smalley et al, ). Sorafenib can be associated with multiple severe adverse cardiovascular effects, including MI and heart failure, (Escalante et al, ), but the underlying mechanisms of these toxicities are not known. In the present study, we identify decreased myocardial function coupled with numerous metabolic changes found in the heart, liver, skeletal muscle and plasma of mice treated with clinically relevant sorafenib doses (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of VEGF signaling with bevacizumab was shown to increase vascular tone and disrupt microvascular blood flow [19, 20]. Clinical consequences of disrupting VEGF signaling include a higher risk for worsening hypertension and a twofold greater risk for heart failure among patients with cancers of solid tumor origin [21, 22]. Among patients undergoing treatment of renal cell carcinoma (RCC) with sorafenib, 68% had some form of cardiovascular toxicity, with most cases (59%) having worsened hypertension.…”
Section: Discussionmentioning
confidence: 99%